ANALISIS PERILAKU INDIVIDU ANGGOTA KOPERASI YANG DIPENGARUHI OLEH BUDAYA ORGANISASI DAN KINERJA PENGURUS - Wulantika, Lita; Wijaya, Henhen (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2018)
Outspoken culture is one of the important things in your organization or company as the organization's culture is a factor affecting the performance and behavior of individuals within an organization. because the organizational culture is not directly regulates each person's attitudes and behavior in accordance with a system of values ​​and norms that guide an organization. The stronger the implementation of the organizational culture the better the performance and behavior of individual members. The method used in this research is descriptive analysis method and verifikatif. The study population was 217 and sample withdrawal technique using stratified random sampling technique to obtain the 69 respondents. Methods of data analysis using linear regression analysis and multiple correlation using the program SPSS 17.0 For Windows. The results of linear regression analysis and multiple correlation there is significant influence of organizational culture on performance management and organizational culture and performance of managers significantly influence the behavior of individual members of the cooperative for 35.4%, and the remaining 64.6% influenced by other factors. Keywords: Organizational Culture, Performance Management, Individual Behavior